Communication Strategy of Tasawuf Underground Community in Da’wah Towards Punk Community - Ade Irfan Abdurahman; Faisal Tomi Saputra (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
This article discusses the communication strategy of the Tasawuf Underground community in da’wah to the punk community. The researcher analyzed the data collected through observation and in-depth interviews with key informants who retained da’wah experience in the Tasawuf Underground community. This study indicates that to preach to the Tasawuf Underground community, a preacher needs to have four things: a) source credibility; in this case, a preacher should have the charisma to influence the audience. b) the introduction of the “road map to home” is a term to invite punk children to study religious knowledge as a provision to return to the afterlife. c) effective communication between da’i and mad’u uses several media, mainly: social media, mass communication media, and interpersonal communication media. d) The message of da’wah is carried out in an informative and persuasive manner; an atmosphere of friendship and kinship is built between the audience and the communicator so that intimacy transpires. They built a communication strategy that resulted in changes in attitudes, actions, and improvements in the punk community members’ quality of life. Credible communicators, understanding audiences, choosing the suitable media and messages, and da’wah messages conveyed in a friendly and familial manner make communicators or preachers competent to influence the punk community in Tebet to return to the path of God and family.